Pilot Study on the Effect of a Single Topical Application of Trichloroacetic Acid 85% on Normal Cervical Tissue - Nuranna, Laila; Lubis, Dolly N.; Arozal, Wawaimuli; Purbadi, Sigit; Barinda, Agian Jeffilano; Purwoto, Gatot; Rustamadji, Primariadewi; Putra, Andi D.; Utami, Tofan W.; Kekalih, Aria (Frontiers in Pharmacology, 2022)
Background: Early detection and treatment of cervical intraepithelial neoplasia (CIN) through a “see and treat” approach is a pillar of cervical cancer prevention programs in developing countries such as Indonesia. One of the major challenges faced is the limited of N2O or CO2 gas supply for cryotherapy. Thus, an alternative therapeutic method such as trichloroacetic acid (TCA) topical application is needed as an alternative solution. The effectiveness of this therapy will depend on its destructive effect on eliminating the whole lesion in CIN. Objective: To estimate the extent of damage in the normal cervical tissue after a single topical application of 85% TCA solution Design and Methods: This research was an intervention study carried out by applying ±5 mL of 85% TCA solution into the cervix of 40 patients scheduled for total hysterectomy for indications other than cervical pathology 24 h before surgery. The extent of tissue destruction was determined microscopically using histopathological specimens. The study protocol is registered at www.clinicaltrial.gov (ID NCT04911075). Results: In the final analysis, 39 subjects were included. The necrotic area was detected at the superficial layer, accompanied by the full epithelial erosion thickness. Additionally, there were also fibrotic areas resembling burned tissue in the stroma. The mean depth of destruction was 1.16 ± 0.01 mm in the anterior lip and 1.01 ± 0.06 mm in the posterior, respectively. There was no significant depth difference between the anterior and posterior lips(p  0.05). Moreover, the 85% TCA topical application was tolerable, as represented by the fact that the vast majority (82.1%) of participants experienced pain with a visual analog scale score of < 4. Conclusion: Single dose of TCA 85% in topical solution was able to destroy the normal cervical tissue with a deeper mean depth than the mean depth of CIN III in squamous epithelium.